Front Cover: Multifunctional Glycoconjugates for Recruiting Natural Antibodies against Cancer Cells (Chem. Eur. J. 68/2019). Issue 68 (24th October 2019) - Liet, Benjamin; Laigre, Eugénie; Goyard, David; Todaro, Biagio; Tiertant, Claire; Boturyn, Didier; Berthet, Nathalie; Renaudet, Olivier
Abstract : The utility of synthetic chemistry in cancer immunotherapy has been demonstrated over the past decades with antitumoral vaccines and antibody recruiting molecules (ARM). By using click chemistry, polyfunctional ARMs composed of multivalent antibody and tumoral binding modules to guide natural antibodies to cancer cells without pre‐immunization step have been developed. The resulting ARM was found to promote the formation of a ternary complex that is required for the stimulation of cytotoxic immune response in vivo. More information can be found in the Full Paper by N. Berthet, O. Renaudet, et al. on page 15508 .